2020
DOI: 10.1021/acsomega.0c03138
|View full text |Cite
|
Sign up to set email alerts
|

Biomimicry Surface-Coated Proppant with Self-Suspending and Targeted Adsorption Ability

Abstract: Proppant is a key material, which can increase the production of unconventional petroleum and gas. Excellent proppants with a long migration distance are required in the fracture network. Resin-coated proppants have been confirmed as a good choice because of the long migration and the self-suspending ability in fracturing fluids. However, the distribution of the resin-coated proppants in fracture networks is random. The design of proppants with targeted adsorption is urgently needed. In this study, a novel pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A polymer is a chemical material composed of a series of smaller monomers covalently bonded, and polymers can be made through addition and condensation reactions. Polymers are classified into organic and inorganic polymers, but they can also be classified into thermosetting polymers and thermoplastic polymers according to their temperature properties. ,, There has been a considerable amount of research on the application of polymers as proppant coatings. ,, …”
Section: Proppant Coating Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A polymer is a chemical material composed of a series of smaller monomers covalently bonded, and polymers can be made through addition and condensation reactions. Polymers are classified into organic and inorganic polymers, but they can also be classified into thermosetting polymers and thermoplastic polymers according to their temperature properties. ,, There has been a considerable amount of research on the application of polymers as proppant coatings. ,, …”
Section: Proppant Coating Materialsmentioning
confidence: 99%
“…In addition, Lan 32 et al reported a magnetic proppant. By adding Fe 3 O 4 nanoparticles to the phenolic resin shell, this proppant can be adsorbed on the magnetic component sites on the surfaces of the fracture network, and its self-suspending ability is five times that of the conventional proppant.…”
Section: Coated Proppantmentioning
confidence: 99%